Factors of PONASI Ecological Complex Resource Degradation - Zougmore, Wend-Kuni Dina Antine; Kabore, Oumar; Dipama, Jean-Marie (European Scientific Journal, ESJ, 2025)
PONASI ecological complex abounds with fauna and floristic species. But these resources are in a phase of degradation. The aim of this study is to analyze the main factors contributing to the degradation of the PONASI ecological complex. In order to assess the degradation factors, a systematic approach was used. It is an approach that takes into account the various phenomena responsible for degradation and the interactions. Data collection techniques focused on documentary research, interviews, field surveys, the use of the snowball sampling method, and the processing of some climatic parameters. For this research, a total of twelve (12) villages were surveyed. The results showed that anthropogenic and climatic factors contribute to the degradation of the resources of the PONASI ecological complex. The anthropogenic factors consist of vegetation fires, excessive wood cutting, grazing, and picking immature fruit, and agricultural front. These factors are exacerbated by the limits of governance which result in a lack of legal texts’ application, a weak appropriation of the decentralization policy by the local authorities. The results of this study have demonstrated that there are a multitude of factors that contribute to the degradation of the PONASI ecological complex. It is urgent to take the necessary measures to reverse this trend of degradation.